The Role of Yersinia enterocolitica O:3 Lipopolysaccharide in Collagen-Induced Arthritis - Katarzyna Kasperkiewicz; Anna S. Świerzko; Marta Przybyła; Janusz Szemraj; Jarosław Barski; Mikael Skurnik; Andrzej Kałużyński; Maciej Cedzyński (Journal of Immunology Research)
Yersinia enterocolitica O:3 is mentioned among the most common arthritogenic pathogens. Bacterial components (including lipopolysaccharide (LPS)) may persist in the joint after eradication of infection. Having an adjuvant activity, LPS may enhance production of anticollagen antibodies, involved in the pathogenesis of rheumatoid arthritis. Furthermore, its ability to activate complement contributes to the inflammation. The aim of this work was to investigate whether Yersinia LPS (coinjected with collagen) is associated with arthritis progression or other pathological effects and to elucidate the mechanism of this association. It was demonstrated that murine mannose-binding lectin C (MBL-C) recognizes the inner core heptoses of the Rd1 chemotype LPS of Yersinia. In addition, the Rd1 LPS activates the MBL-associated serine protease 1 (MASP-1) stronger than the S and Ra chemotype LPS and comparable to Klebsiella pneumoniae O:3 LPS. However, in contrast to the latter, Yersinia Rd1 LPS was associated neither with the adjuvancity nor with the enhancement of pathological changes in animal paws/impairment of motility. On the other hand, it seemed to be more hepatotoxic when compared with the other tested endotoxins, while the enlargement of inguinal lymph nodes and drop in hepatic MBL-C expression (at the mRNA level) were independent of LPS chemotype. Our data did not suggest no greater impact Y. enterocolitica O:3 on the development or severity of arthropathy related to anticollagen antibody-induced arthritis in mice, although its interaction with MBL-C and subsequent complement activation may contribute to some adverse effects.